Soteriological Perspectives in Hindu Religion and Culture - Jacob S Plamthodathil (Journal of Dharma, 1987)
The comment that 'India lives in fifty centuries' seems to summarise the characteristic of infinite variation one comes across in the nature of Hindu Religion and Indian culture. The contribution to religious principles and practices of Hinduism came from a wide variety of sources, peoples and spreads over centuries of human existence on the subcontinent. It has yielded a spectrum of an highly enriched heritage of colourful and complex aspects of religion and culture. Therefore, the task of identifying soteriological perspectives in every sect, school and individual variation will remain incomplete. For the present analysis, the perspectives are identified through the blending of the multiplicity of doctrines, seers and practices. They lead to the well known characteristic of Hinduism, namely, 'Unity in Diversity'.